Multivariate analysis of lactose content in milk of Holstein and Jersey cows1 - Alessio D.R.M.* (2016)
This study evaluated the factors influencing the variation in the lactose content of milk in Holstein and Jersey herds in Santa Catarina, southern Brazil, using multivariate analysis. Data from 73 dairy herds in the Dairy Herds Improvement Program of the State of Santa Catarina were provided by the Santa Catarina Association of Cattle Breeders (ACCB). A total of 46,242 monthly records of Holstein and Jersey (59 and 41 % of the total records, respectively) cows from 2009 to 2012 were analyzed using multiple correspondence, factor, and cluster analyses. Lactose content was observed to correlate with somatic cell count and parity, whereas the evaluated breeds, as well as the production and concentrations of fat and protein in the milk, were not associated with the lactose content. The cows were categorized into three groups, the first consisting of cows of both breeds with low lactose content (4.19), high somatic cell score (5.82), and higher parity (2.50), contrasting with two other groups each with mean values characteristic for Holstein and Jersey breeds, respectively. Analysis of cows without subclinical mastitis (<200,000 somatic cells ml-1) revealed that the relationship of parity with lactose level was independent of the effect of somatic cells. Lactose contents less than 4.4 % were observed in autumn. Overall, the present study suggests that the lactose content of milk is influenced by somatic cell count and parity and that it varies seasonally; however, it is not related to breed, milk yield, milk fat content, or milk protein level.